2020
DOI: 10.1097/wnp.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Adaptive Ten Ten: Proposal for Electrode Nomenclature for High-Density EEG

Abstract: Purpose: High-density EEG (HD-EEG) systems and electrical source imaging techniques have revolutionized our ability to assess the potential sources of epileptiform activity and other EEG features. Nonetheless, clinical use of HD-EEG is hampered by the lack of a standardized electrode nomenclature system and the inherent difficulties encountered in visually reviewing recordings. Inefficient visual review of HD-EEG remains a major barrier to incorporating these techniques into routine clinical care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The cerebellar extension was designed by completing the population of the Iz row, labelled using the standard nomenclature, from P9 to P10, and adding two additional 10% rows inferiorly, from P11 to P12 and from P13 to P14. Subsequent to the cap design, Heine et al (2020) published an extended electrode placement nomenclature which we have adopted here. The electrodes were Ag/ AgCl type and maintained at 10 kOhms or less.…”
Section: Eeg/eceg Recordingmentioning
confidence: 99%
“…The cerebellar extension was designed by completing the population of the Iz row, labelled using the standard nomenclature, from P9 to P10, and adding two additional 10% rows inferiorly, from P11 to P12 and from P13 to P14. Subsequent to the cap design, Heine et al (2020) published an extended electrode placement nomenclature which we have adopted here. The electrodes were Ag/ AgCl type and maintained at 10 kOhms or less.…”
Section: Eeg/eceg Recordingmentioning
confidence: 99%
“…EEG/ECeG Recording EEG was recorded using a 104 (96 cap + 8 external, EasyCap GmbH) channel custom 10% cerebellar extension montage designed by completing the population of the Iz circle, and then two additional 10% rows below, as described in Heine et al (2020). ActiveTwo ampli ers (BioSemi, Holland) were used.…”
Section: Subjectsmentioning
confidence: 99%
“…Other studies reported positive individual components around 40 ms following whole-body rotations [( 163 ); 38.9 ms] and translations [( 33 , 166 , 167 ); p38.2 ms under parietal electrodes]. More recently, IAS on the left mastoid was also found to evoke n25, p40, and n53 components under Bz, an electrode placed over the cerebellum, two rows below Iz at the midline [( 150 ); following a nomenclature proposed by Heine et al ( 168 )].…”
Section: Middle Latency Vestibular-evoked Potentialsmentioning
confidence: 99%